Novel penile circumcision suturing devices versus the shang ring for adult male circumcision: a prospective study - Han,Hu (2017)
ABSTRACT Introduction To evaluate the safety and efficacy of a novel penile circumcision suturing devices PCSD and Shang ring (SR) for circumcision in an adult population. Materials and Methods A total of 124 outpatients were randomly assigned to receive PCSD (n=62) or SR (n=62). Patient characteristics, operative time, blood loss, return to normal activities time (RNAT), visual analogue scale (VAS), scar width, wound healing time, cosmetic result, and complications were recorded. Results There were no significant differences in blood loss, RNAT, or complications between the two groups. There were no significant differences in the VAS scores at the operation, at 6 or 24 hours after surgery (P>0.05). The wound scar width was wider in the SR group than in the PCSD group (P<0.01). Patients in the SR group had significantly longer wound healing time compared with those in the PCSD group (P<0.01). Patients who underwent PCSD were significantly more satisfied with the cosmetic results (P<0.01). Conclusions SR and PCSD are safe and effective minimally invasive techniques for adult male circumcision. Compared with SRs, PCSDs have the advantages of faster postoperative incision healing and a good effect on wound cosmetics.